Detection of Phytophthora nicotianae in water used for irrigating citrus trees by Ypt1 gene based nested PCR - S.G. NERKAR and ASHOK KUMAR, A.K. DAS*, S.S. BAWAGE, (Indian Phytopathology, 2013)
Phytophthora nicotianae is a very common and destructive pathogen of numerous field and horticultural crops such as citrus. The present study assessed Ypt1 gene specific primers for detection of P. nicotianae in citrus irrigation water using a nested polymerase chain reaction (PCR) assay. The assay detected the pathogen in naturally infested water samples collected from orchard basin more rapidly and accurately than standard isolation methods. This PCR based detection for P. nicotianae in contaminated irrigation water will serve as a reliable method for phytosanitary programme in citriculture.